2010
DOI: 10.1177/0022034510363220
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetics Inhibit Ca-ATPase in Masticatory Muscles

Abstract: Local anesthetics have myotoxic effects and inhibit Ca-ATPase activity and Ca transport in skeletal muscles. Such effects have not been fully elucidated in masticatory muscles. We tested the hypothesis that local anesthetics increase myoplasmic calcium in masticatory muscles by inhibiting Ca-ATPase at a concentration similar to that of dental cartridges. The effects of lidocaine and bupivacaine on Ca-ATPase from rabbit masseter and medial pterygoid muscles were tested with radioisotopic and colorimetric method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Other studies have suggested an inhibition of Ca 2+ reuptake into the sarcoplasmic reticulum, possibly regulated by Ca 2+ ATPase activity [34,36]. Besides dysregulated intracellular Ca 2+ , the involvement of ROS production is another possible mechanism of LA-induced cell death [37,38].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies have suggested an inhibition of Ca 2+ reuptake into the sarcoplasmic reticulum, possibly regulated by Ca 2+ ATPase activity [34,36]. Besides dysregulated intracellular Ca 2+ , the involvement of ROS production is another possible mechanism of LA-induced cell death [37,38].…”
Section: Discussionmentioning
confidence: 97%
“…It is postulated in myocytes that LA induce Ca 2+ release from the sarcoplasmic reticulum by interaction with ryanodine receptors [34,35]. Other studies have suggested an inhibition of Ca 2+ reuptake into the sarcoplasmic reticulum, possibly regulated by Ca 2+ ATPase activity [34,36]. Besides dysregulated intracellular Ca 2+ , the involvement of ROS production is another possible mechanism of LA‐induced cell death [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…12,24 Secondly, muscular stiffness is also linked to the myotoxic effects of anesthetics resulting in degenerative changes in masseter and medial pterygoid. 12,25 Another usual post-operative clinical complication, following a palatine block, is the occurrence of palatal ulceration or tissue necrosis, which is caused by anesthetic toxicity or high concentration of vasoconstrictors. 26 Two limitations in implementing this study design were the use of the same anesthetic agent in the same concentration along with epinephrine, thus higher concentrations of lidocaine could not be evaluated neither estimation of their individual toxic effect was possible.…”
Section: Discussionmentioning
confidence: 99%
“…15,30,33e38,41,43 These mechanisms are thought to be related to LA interference with ATP phosphorylation. 37,41,43 A surge in myoblastic apoptosis is the sequela of LA exposure. 1,19e23,25e29 Apoptosis is triggered by increased Back muscles, 37 back leg muscles, 43 breast muscle, 28 C2C12 cell line, 18e23,25,26 oesophageal muscle, 24 extensor digitorum longus muscle, 1,24,35,36 first lumbrical of foot muscle, 27 flexor digitorum brevis muscle, 24 hind leg muscles 15,32,33,42 masseter muscle, 34,37,41 medial pterygoid, 37,38,41 psoas muscle 40 quadriceps muscle, 29 skeletal muscle, 13,30,31 soleus muscle, 1,24 temporalis muscle, 39 tibialis anterior muscle 1 Humans, 13,29 mice, 1,18e26,35,36 quail, 28 rats, 27 pigs, 42 rabbits 15,30e34,37e41,43 Articaine, 38 benzocaine, 32 bupivacaine, 1,13,18e21,23e29,34,35,41e43 bupivacaine S and R enantiomers, 35,36 bupivacaine with caffeine, 1 bupivacaine with dantrolene...…”
Section: Myotoxic Damagementioning
confidence: 99%